Analisis Konsentrasi SO2 dan CO Menggunakan Model Gaussian Line Source Di Udara Ambien - Ridwan Syahputra Samosir; Ivan Indrawan; Isra Suryati; Hendri Irwandi (Jurnal Dampak, 2018)
Purpose of this study to analyze concentration of SO2 and CO at Tanjung Morawa Toll Gate and Amplas Toll Gate with Gaussian Line Source modeling. Based on the measurement of ambient roadside air quality at Tanjung Morawa Toll Gate and Amplas Toll Gate, CO and SO2 concentrations still meet the ambient air quality standard according to PP. 41 year 1999. The highest concentration of CO at Tanjung Morawa Toll Gate is 447,06 μg/m3 and at Amplas Toll Gate is 389,54 μg/m3 while The highest concentration of SO2 at Tanjung Morawa Toll Gate is 97,7 μg/m3 and at Amplas Toll Gate is 62.51 μg /m3. Based on the calculation using Gaussian Line Source model, the highest CO concentration at Tanjung Morawa Toll Gate is 263,16 μg/m3 and at Amplas Toll Gate is 258,16 μg/m3 while The highest concentration of SO2 at Tanjung Morawa Toll Gate is 1,64 μg /m3 and at Amplas Toll Gate is 1.32 μg/m3. validation test results with IOA, NMSE, FB, and Fa2, Gaussian Line Source model can be applied at Tanjung Morawa Toll Gate and Amplas Toll Gate for CO parameters. Meanwhile Gaussian Line Source model can not be applied for SO2 parameters at Tanjung Morawa Toll Gate and Toll Gate of Amplas.